Navigating Linguistic Challenges: The Use Of Balinese Terminologies By Tourism Actors In Rural Villages - Damayanti, Luh Sri; Pratama, I Wayan Adi; Wibawa, I Ketut (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
The massive growth of tourism villages in Bali is not echoed by the development of quality of the local community. One biggest challenge faced by local community in running the tourism was English competence. This research aimed at identifying the use of English in tourism villages and the challenges encountered by tourism actors in tourism villages in Bali. The research was qualitative research involving 19 informants. Data were obtained vi written interviews and analysed qualitatively. The results revealed that English is used to do general communication, sell tickets, do upselling, explain the villages, do correspondence, and handle complaints. In the communication, the tourism actors encountered 2 categories of barriers which were cultural barrier & language barrier. The cultural barrier was represented by the difficulty in explaining Balinese local terminologies and the difficulty to understand tourists’ utterances due to different accents. Meanwhile the language barrier wasclearly seen by the limited English vocabulary that they mastered.